Effect of fiber angle alignment on energy absorbing behavior of conical composite tubes. Issue 4 (15th July 2022) - Meriç, Dursun; Gedikli, Hasan
Abstract: In this study, the effect of fiber angle alignment on the energy-absorbing behavior of 0°, 5° and 10° conical CFRP tubes was numerically investigated. Feedforward Neural Networks (FFNN) were used to determine the optimum fiber angle alignment for the highest absorbed energy (AE), crash force efficiency (CFE), and lowest peak force. In addition, 100, 400, 600, and 800 kg/m3 metallic foam filling was used to investigate the foam filling effect in tubes with an optimum fiber angle alignment. The results showed that the amount of absorbed energy can increase by up to 118% with optimum fiber alignment.